Draft genome sequence of the rubber tree Hevea brasiliensis - Rahman, Ahmad Yamin Abdul; Usharraj, Abhilash O; Misra, Biswapriya B; Thottathil, Gincy P; Jayasekaran, Kandakumar; Feng, Yun; Hou, Shaobin; Ong, Su Yean; Ng, Fui Ling; Lee, Ling Sze; Tan, Hock Siew; Sakaff, Muhd Khairul Luqman Muhd; et al. (BMC genomics, 2013)
Background Hevea brasiliensis, a member of the Euphorbiaceae family, is the major commercial source of natural rubber (NR). NR is a latex polymer with high elasticity, flexibility, and resilience that has played a critical role in the world economy since 1876. Results Here, we report the draft genome sequence of H. brasiliensis . The assembly spans ~1.1 Gb of the estimated 2.15 Gb haploid genome. Overall, ~78% of the genome was identified as repetitive DNA. Gene prediction shows 68,955 gene models, of which 12.7% are unique to Hevea . Most of the key genes associated with rubber biosynthesis, rubberwood formation, disease resistance, and allergenicity have been identified. Conclusions The knowledge gained from this genome sequence will aid in the future development of high-yielding clones to keep up with the ever increasing need for natural rubber.